Peter Beinart, "Being Jewish after the Destruction of Gaza : A Reckoning", New York, Alexander A. Knopf, 2025, 192 p. - David NEUHAUS (Proche-Orient Chrétien, 2025)
Since October 7, 2023, Israel/Palestine and the surrounding countries have been swallowed up in a new round of violence and suffering.One flickering light in this somber landscape is the voice of dissent on the margins of Jewish society, opposing the war and the destruction of Gaza.[...]